Законы о „национальном уравненииˮ в Моравии 1905 г., на Буковине 1910 г. и в Галиции 1914 г.: сравнительная характеристика - Ульяна Уская (Codrul Cosminului, 2016)
The article presents the essence of the concept of “national equalization”, based on a comparative analysis of the reforms of regional statutes and regional election orders in Moravia (1905), Bukovina (1910) and Galicia (1914). We have explained the features of reforms of local political systems in view of the interethnic and inter-confessional relations in the above-mentioned Austrian provinces. In addition, the analysis aimed to evaluate the impact of the “national levelling” on the potential interethnic conflict, in terms of intensification of national movements before the World War I.